The development and validation of a new technology, based upon 1.5% arginine, an insoluble calcium compound and fluoride, for everyday use in the prevention and treatment of dental caries - Cummins, D. (Journal of dentistry, 2013)
This paper briefly discusses caries prevalence, the multi-factorial nature of caries etiology, caries risk and the role and efficacy of fluoride. The paper also highlights research on bacterial metabolism which provided understanding of the mouth's natural defenses against caries and the basis for the development of a new technology for the everyday prevention and treatment of caries. Finally, evidence that the technology complements and enhances the anti-caries efficacy of fluoride toothpaste is summarized. Global data show that dental caries is a prevalent disease, despite the successful introduction of fluoride. Caries experience depends on the balance between consumption of sugars and oral hygiene and the use of fluoride. Three scientific concepts are fundamental to new measures to detect, treat and monitor caries: (1) dental caries is a dynamic process, (2) dental caries is a continuum of stages from reversible, pre-clinical to irreversible, clinically detectable lesions, and (3) the caries process is a balance of pathological and protective factors that can be modulated to manage caries. Fluoride functions as a protective factor by arresting and reversing the caries process, but fluoride does not prevent pathological factors that initiate the process. A novel technology, based upon arginine and an insoluble calcium compound, has been identified which targets dental plaque to prevent initiation of the caries process by reducing pathological factors. As the mechanisms of action of arginine and fluoride are highly complementary, a new dentifrice, which combines arginine with fluoride, has been developed and clinically proven to provide superior caries prevention.